High winter ozone pollution from carbonyl photolysis in an oil and gas basin - Edwards, Peter M.; Brown, Steven S; James M. Roberts; Ahmadov, Ravan; Banta, Robert M.; de Gouw, Joost A.; Dube, William P.; Field, Robert A.; Flynn, James H.; Gilman, Jessica B.; Graus, Martin; Helmig, Detlev; et al. (NATURE, 2014)
The United States is now experiencing the most rapid expansion in oil and gas production in four decades, owing in large part to implementation of new extraction technologies such as horizontal drilling combined with hydraulic fracturing. The environmental impacts of this development, from its effect on water quality(1) to the influence of increased methane leakage on climate(2), have been a matter of intense debate. Air quality impacts are associated with emissions of nitrogen oxides(3,4) (NOx = NO + NO2) and volatile organic compounds(5-7) (VOCs), whose photochemistry leads to production of ozone, a secondary pollutant with negative health effects(8). Recent observations in oil-and gas-producing basins in the western United States have identified ozone mixing ratios well in excess of present air quality standards, but only during winter(9-13). Understanding winter ozone production in these regions is scientifically challenging. It occurs during cold periods of snow cover when meteorological inversions concentrate air pollutants from oil and gas activities, but when solar irradiance and absolute humidity, which are both required to initiate conventional photochemistry essential for ozone production, are at a minimum. Here, using data from a remote location in the oil and gas basin of northeastern Utah and a box model, we provide a quantitative assessment of the photochemistry that leads to these extreme winter ozone pollution events, and identify key factors that control ozone production in this unique environment. We find that ozone production occurs at lower NOx and much larger VOC concentrations than does its summertime urban counterpart, leading to carbonyl (oxygenated VOCs with a C=O moiety) photolysis as a dominant oxidant source. Extreme VOC concentrations optimize the ozone production efficiency of NOx. There is considerable potential for global growth in oil and gas extraction from shale. This analysis could help inform strategies to monitor and mitigate air quality impacts and provide broader insight into the response of winter ozone to primary pollutants.